Fiqh Learning Process Based on Constructivism Theory at MA Mambaul Ulum Megaluh - M. Dzikrul Hakim Al ghozali; Dita Meilawati (SCHOOLAR: Social and Literature Study in Education, 2021)
This study aims to determine the learning process of PAI based on Constructivism theory at MA Mambaul Ulum Megaluh. This article discusses the learning process in Islamic Religious Education subjects, especially Fiqh subjects based on constructivism theory at MA Mambaul Ulum Megaluh. This study also examines what is problematic in the Fiqh learning process at MA Mambaul Ulum Megaluh. This research is a descriptive qualitative research. Data collection techniques in this study are: 1) Observation 2) Interview; 3) Documentation.Then the data obtained will be drawn conclusions using triangulation techniques. Triangulation technique is to draw solid conclusions not only from one point of view. The results of this study indicate that the learning activities carried out in the learning process consist of 3 activities, namely initial activities, core activities, and closing activities. The process of learning Fiqh at MA Mambaul Ulum Megaluh uses conventional methods (lectures) and discussions or demonstrations in practical learning. Or students can be given the freedom to study outdoors by seeking their own experiences. Meanwhile, the problems faced are the ability to process information for each student who is different and the supporting infrastructure for Fiqh learning activities is inadequate.